When does FDI make a difference for growth? A comparative analysis of resource‐rich and resource‐scarce African economies. (3rd November 2022) - Yimer, Addis
Abstract: This study revisits the foreign direct investment (FDI)–growth nexus in Africa, categorizing countries as resource‐rich or resource‐scarce for the period 2000–2017 in an attempt to capture the impact that cross‐country natural resource endowment differences may have on the FDI–growth relationship. Thus, the study is an attempt to answer the question: Does being a natural resource‐abundant or resource‐scarce country alter the FDI‒growth nexus? Using the System Generalized Method of Moments, it is found that the effects of FDI on economic growth vary depending on countries' resource richness. While FDI affects growth positively and significantly in the resource‐scarce category, the size of such an effect varies across countries within the group. The better the human capital and institutions, the higher the FDI‐induced growth. However, no effect of FDI on growth has been identified for the resource‐rich category. The findings suggest that African countries in general, and resource‐rich economies in particular, need to look carefully and critically at the type of FDI inflows they receive.